Corporate balance sheets in developed economies: Implications for investment - Denise Côté; Christopher Graham (Bank of Canada, 2007)
In this paper, the authors examine the aggregate national balance-sheets of non-financial corporations in Australia and the G7 countries with a view to assessing both their financial structure and their financial position. More importantly, the authors investigate whether the financial position of non-financial corporations (i.e., debt-to-equity ratio) is material to the economy's investment prospects and whether the importance of this channel differs depending on the structure of corporate financing i.e., bank-based or market-oriented financing structures. Based on a dynamic business investment error-correction model that controls for the opportunity cost of capital and output growth, the authors test the above hypotheses using a quarterly panel dataset of eight developed economies over the 1992-2005 period. Their empirical results suggest that the financial position of non-financial corporations has a statistically significant impact on aggregate business investment growth, although the effect is quantitatively modest. Thus, their findings are consistent with the prediction of models that feature credit market imperfections such as costly information and asymmetric information. Moreover, the effect of corporate financial position appears to be statistically equivalent regardless of whether a country's corporations predominantly finance their investments through bank borrowing or market-oriented financing.
Keywords: E22; E32; E44; 330; Business fluctuations and cycles; International topics; Bilanz; Betriebliche Finanzwirtschaft; Kapitalstruktur; Investition; Unternehmensfinanzierung; Industriestaaten